A mechanistic force model for simulating haptics of hand-held bone burring operations. (November 2017) - Danda, Avinash; Kuttolamadom, Mathew A.; Tai, Bruce L.
Highlights: This paper introduced a mechanistic force model to estimate the force experienced during high-speed burring in a three-dimensional setting. The force model was considered with both accuracy and simplicity for the development of real-time haptic rendering. The force model was developed and experimentally validated with different burring tool angles and feed motions on a synthetic bone. The advantages and limitations of this model were discussed in the paper. Abstract: This paper presents a mechanistic model to predict the forces experienced during bone burring with application to haptic feedback for virtual reality surgical simulations. Bone burring is a hand-held operation where the force perceived by the surgeon depends on the cutting tool orientation and motion. The model of this study adapted the concept of specific cutting energy and material removal rate based on machining theory to calculate force distribution on the spherical tool surface in a three-dimensional setting. A design of experiments with three tool cutting angles and three feed motions was performed to calibrate and validate the model. Despite some variance in the results, model predictions showed similar trends to experimental force patterns. While the actual force profile also exhibits significant oscillation, the dominant frequencies of this oscillating force component were found to be independent of cutting and non-cutting instances, and hence could be imposed as a uniform background signal. Though the presented model is primarily applicable to abrasive burrs, it has far-reaching applications within other types of surgical simulations as well.